Frequency distribution of six cytokine gene polymorphisms in North‐ and South‐Italy. (26th May 2017) - Santovito, A.; Gendusa, C.; Matini, A.; Ferraro, F.; Musso, I.; Costanzo, M.; Delclos, A.; Cervella, P.
Summary: Allelic and genotype frequencies of four cytokine genes were obtained from 738 subjects from North‐ and South‐Italy. Populations were in Hardy–Weinberg equilibrium for all genes but significantly differed in the frequency of all SNPs and three haplotypes. In the MDS graph, they were plotted in separate positions close to Europeans and an Ivorian population, respectively.